2018
DOI: 10.1080/11356405.2018.1494773
|View full text |Cite
|
Sign up to set email alerts
|

Teaching-learning methods and their effect on professional development and the development of graduates’ competencies / Métodos de enseñanza-aprendizaje y su efecto en el desarrollo profesional y competencial de los egresados

Abstract: This article analyses the effect of the teaching-learning methods used in Spanish universities on three measures of educational output: average mark, graduates' assessment of their professional performance in different dimensions, and their assessment of the acquisition of professional competencies and skills. Multi-level models were used in which graduates (first level) are grouped by field of study (second level). The Class attendance and Written work methods have the most influence on the average mark but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
2
0
8
Order By: Relevance
“…Empirical findings in recent years have provided detailed information on how the learning opportunities presented in training programs have a notable correlation with the knowledge and skills of teachers at the end of their training [10,11]. A recent study by Coll, Pardo and Pérez [12] has shown the close correlation between the methodology employed in university classes and the professional development and skills of graduates. Problem-based learning, teaching practice, and practical knowledge were shown to be among the most influential factors.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical findings in recent years have provided detailed information on how the learning opportunities presented in training programs have a notable correlation with the knowledge and skills of teachers at the end of their training [10,11]. A recent study by Coll, Pardo and Pérez [12] has shown the close correlation between the methodology employed in university classes and the professional development and skills of graduates. Problem-based learning, teaching practice, and practical knowledge were shown to be among the most influential factors.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of the lecture method and the relative advantages of alternative pedagogical approaches have been highlighted by many authors (e.g., Bartholomay 2018;Clark and Foster 2017;Coll-Serrano et al 2018;Eglitis et al 2016;Ilter 2014;Larmer 2015;Lazonder and Harmsen 2016;Pedaste et al 2015;Wijnen et al 2017). These analysts criticize the one-way flow of information from lecturer to student and its production of low levels of student engagement in lecture-based teaching systems, manifested in poor attendance or lack of attention during class (Huggins and Stamatel 2015;Sagy et al 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tradicionalmente "evaluar" era poner una nota final al alumno, pero no una tarea (Trigueros Cervantes, Rivera García y De la Torre Navarro, 2012): "cuyo objetivo es la valoración del proceso de enseñanza y aprendizaje llevado a cabo" (p. 480). Los métodos de enseñanza-aprendizaje en la universidad española tienen efecto sobre el rendimiento académico medido a través de la nota media (Coll-Serrano, Pardo-García y Pérez, 2018).…”
Section: Antecedentesunclassified
“…Tras el estudio realizado, podemos afirmar que la evaluación continua favorece el aprendizaje en las asignaturas de contabilidad financiera, lo que se refleja en la nota del examen final, tal y como comprueban también otros autores como Cano (2011), Fraile et al (2013), López-Pastor (2011), y Moro-Egido (2016), o que los métodos de enseñanza-aprendizaje tienen efecto en la nota media como obtienen Coll-Serrano et al (2018). En nuestro caso efectivamente la nota de la evaluación continua explica en una parte importante (el coeficiente obtenido en el modelo de regresión es 0.582) la nota del examen final, por lo que claramente si el alumno ha aprovechado la evaluación continua para su aprendizaje esto repercutirá positivamente en su nota (Se comprueba la hipótesis H 1 ).…”
Section: Conclusionesunclassified